2013
DOI: 10.1007/s40544-013-0032-0
|View full text |Cite
|
Sign up to set email alerts
|

Abrasive-free polishing of hard disk substrate with H2O2-C4H10O2-Na2S2O5 slurry

Abstract: Abstract:The effect of tert-butyl hydroperoxide-sodium pyrosulfite ((CH 3 ) 3 COOH-Na 2 S 2 O 5 ) as an initiator system in H 2 O 2 -based slurry was investigated for the abrasive-free polishing (AFP) of a hard disk substrate. The polishing results show that the H 2 O 2 -C 4 H 10 O 2 -Na 2 S 2 O 5 slurry exhibits a material removal rate (MRR) that is nearly 5 times higher than that of the H 2 O 2 slurry in the AFP of the hard disk substrate. In addition, the surface polished by the slurry containing the initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…As an ultra-precision processing technique, chemical mechanical polishing (CMP) technique has been widely used in semiconductor fabrication. CMP combines the synergistic effect of chemical etching and mechanical abrasion, and can achieve both local and global planarization of the substrate surface [14][15][16][17]. Recently, the application of CMP technique has been extended to other areas, such as high value-added and precise instruments.…”
Section: Introductionmentioning
confidence: 99%
“…As an ultra-precision processing technique, chemical mechanical polishing (CMP) technique has been widely used in semiconductor fabrication. CMP combines the synergistic effect of chemical etching and mechanical abrasion, and can achieve both local and global planarization of the substrate surface [14][15][16][17]. Recently, the application of CMP technique has been extended to other areas, such as high value-added and precise instruments.…”
Section: Introductionmentioning
confidence: 99%
“…10 As is revealed, chemical mechanical polishing (CMP) combines the synergetic effects of chemical corrosion and mechanical abrasion, and can achieve both local and global planarization of the substrate surface. [11][12][13][14] Hu et al 2 used colloidal silica as the abrasive and investigated the effects of pH and oxidizer on the polishing performance of stainless steel, and it was reported that the combination of oxidizer and strong acidity was the prerequisite for high material removal rate (MRR). However, the microscopic defects of 1-2 μm in size cannot be effectively avoided on the polished surface.…”
mentioning
confidence: 99%
“…The addition of free radical scavenger in the polishing slurry can effectively inhibit the chemical action of free radicals on the crystal surface . After polishing for 1 h, the MMR and the variation pattern of surface roughness Sa with polishing time of three groups of experiments are shown in Figure .…”
Section: Resultsmentioning
confidence: 99%